Qualitative analysis of histochemical and immunohistochemical properties of ethanol, glycerol, and formalin fixative - Buvaneswari V,; Deepadevi G,; Peter Samidoss A,; Muthu Prabha MS,; Vinoth Kumar V, (Asian Journal of Medical Sciences, 2025)
Background: Fixation is essential in histopathology to preserve tissue integrity before analysis, with neutral buffered formalin being the gold standard for decades because of its effective protein cross-linking properties. Aims and Objectives: This study aimed to evaluate the histochemical and immunohistochemical properties of ethanol, glycerol, and formalin (EGF) fixative and to compare and analyze the impact of fixation using conventional formalin and EGF fixative on special histochemical stains and immunohistochemical studies. Materials and Methods: A minimal formalin containing EGF fixative was prepared with a specific concentration of EGF and hypotonic saline. Tissue specimens were collected directly from the surgical operation theatre and were fixed in EGF fixative and formalin fixative. After fixation and processing, the tissues were subjected to various Histochemical stains, including periodic-acid Schiff (PAS), Alcian blue-PAS, Alcian blue, Masson’s Trichrome, Van Gieson, and Reticulin, along with immunohistochemical staining for E-cadherin, human epidermal growth factor receptor 2/neu, and Ki-67. Comparative analyses were done for both fixatives on histochemical and immunohistochemistry stains. Results: This study assessed the efficacy of EGF fixative and is compared with conventional formalin for histochemical and immunohistochemical stains which was found to be effective. This minimal formalin-containing EGF fixative was qualitatively comparable to conventional formalin fixative for histochemical and immunohistochemical stains. Conclusion: EGF fixative is a safe alternative to conventional formalin for routine histochemical and immunohistochemical staining, offering a means to mitigate the health risks associated with formalin exposure among health-care professionals.